Eco-environmental quality assessment of the artificial oasis of Ningxia section of the Yellow River with the MRSEI approach - Dong, Chunyuan; Qiao, Rongrong; Yang, Zhicheng; Luo, Lihui; Chang, Xueli (Frontiers in Environmental Science, 2023)
Knowing how the artificial oasis is changing is important for maintaining regional sustainable development in the arid region. However, a rapid and reliable assessment approach remains to be developed in assessing environment quality. We employed MRSEI to analyze the eco-environment quality in the artificial oasis of Ningxia section of Yellow River. LDI was a unique expression of heterogeneity (diversity). In the study area, in the year with low MRSEI (2000), the area with medium and general grades was larger than the area with other grades, and in the year with high MRSEI (2020), the area with medium and general grades was larger than the area with other grades. The period 2000-2020 is characterized by the transition of "poor" and "fair" grades to neighboring higher grades. The composition and pattern of land use types also had indirect effects on the MRSEI of artificial oases. These findings indicate that the improvement of ecological and environmental quality from 2000 to 2020 was mainly caused by the transfer of Poor and Fair grades to neighboring higher grades, and MRSEI is a more effective method to evaluate the ecological and environmental quality of artificial oases